Krisis Kebudayaan Islam dan Gagasan Ismail Raji Al-Faruqi - Farkhan Fuady (Universitas Islam Negeri Raden Mas Said Surakarta, 2022)
Culture in the community environment develops and is preserved by the community. More and more these cultures interact with other cultures. These interactions lead to a cultural crisis, in which social changes occur that lead to a decline. Ismail Raji al-Faruqi is one of the leading Muslim scholars who initiated Islamic culture. This article aims to describe the idea of Ismail Raji al-Faruqi's Islamic culture. The idea is expected to be able to answer the phenomenon of the cultural crisis. By using descriptive analysis, this article shows that al-Faruqi's idea of Islamic culture basically focuses on seeing people's awareness of Islamic values. Muslims are expected to realize that they are creatures of God.